Pigmented fungiform papillae of the tongue in a Saudi woman - Nouf Alzahrani; Ruaa Alharithy (Wolters Kluwer Medknow Publications, 2018)
Pigmented fungiform papillae of the tongue are a benign condition that is characterized by pigmentation involving the fungiform papillae. Our patient is a 25-year-old female who has an asymptomatic pigmentation over the tongue for 13 years. Examination showed pigmentation confined to the fungiform papillae on the dorsum of the tongue. The diagnosis of pigmented fungiform papillae of the tongue was made clinically. The patient was reassured and was given a 3-month follow-up. We are reporting this case to increase the awareness of this diagnosis and to avoid unnecessary workup.